Network-Cloud Slicing Definitions for Wi-Fi Sharing Systems to Enhance 5G Ultra Dense Network Capabilities. (3rd February 2019) - Carmo, Maxweel; Dantas Silva, Felipe S.; Neto, Augusto Venâncio; Corujo, Daniel; Aguiar, Rui
Abstract : Ultradense Networks (UDNs) seek to scale the 5th-Generation mobile network systems at unforeseen amounts of networks, users, and mobile traffic. We believe that the Wi-Fi sharing service is an asset in expanding 5G UDN capacity requirements for higher coverage and ubiquitous wireless broadband connectivity. However, the limitations of the Wi-Fi sharing pioneer deployment, along with other related works, has led our team to carry out further research. As a result, it was found that FOg CloUd Slicing for Wi-Fi sharing (FOCUS) is a suitable means of expanding 5G UDN capacities. FOCUS applies end-to-end Network-Cloud slice definitions on top of the Wi-Fi sharing technology, with the aim of offering multitenancy and multiservice support for a wide range of services, while meeting carrier-grade requirements and resource control at runtime and making full use of a "softwarized" approach. The feasibility of the FOCUS system is assessed in a real testbed deployment prototype, which allows an accurate view to be obtained of the basic functional principles and system-level proof-of-concept alongside the FON de facto Wi-Fi sharing service. The results suggest that FOCUS offers much greater benefits than FON, owing to its capacity to provide end-to-end Network-Cloud Slices while ensuring independent/isolated service delivery with resource adaptation at runtime.